(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
With the launching of the cluster development programme in India by the UNIDO in 1997, promoting clusters as a strategy to enhance the competitiveness and to participate in the global value chain has been almost a celebrated strategy countrywide. The surge of various cluster schemes can be observed since 2000 onwards. Numerous Government and quails-government documents have acknowledged cluster development as the most important initiative to improve the performance of the MSMEs in the country.